Aligning graphene in bulk copper: Nacre-inspired nanolaminated architecture coupled with in-situ processing for enhanced mechanical properties and high electrical conductivity. (June 2017) - Cao, Mu; Xiong, Ding-Bang; Tan, Zhanqiu; Ji, Gang; Amin-Ahmadi, Behnam; Guo, Qiang; Fan, Genlian; Guo, Cuiping; Li, Zhiqiang; Zhang, Di
Abstract: Methods used to strengthen metals generally also cause a pronounced decrease in ductility and electrical conductivity. In this work a bioinspired strategy is applied to surmount the dilemma. By assembling copper submicron flakes cladded with in-situ grown graphene, graphene/copper matrix composites with a nanolaminated architecture inspired by a natural nacre have been prepared. Owing to a combined effect from the bioinspired nanolaminated architecture and improved interfacial bonding, a synergy has been achieved between mechanical strength and ductility as well as electrical conductivity in the graphene/copper matrix composites. With a low volume fraction of only 2.5% of graphene, the composite shows a yield strength and elastic modulus ∼177% and ∼25% higher than that of unreinforced copper matrix, respectively, while retains ductility and electrical conductivity comparable to that of pure copper. The bioinspired nanolaminated architecture enhances the efficiencies of two-dimensional (2D) graphene in mechanical strengthening and electrical conducting by aligning graphene to maximize performance for required loading and carrier transporting conditions, and toughens the composites by crack deflection. Meanwhile, in-situ growth of graphene is beneficial for improving interfacial bonding and structural quality of graphene. The strategy sheds light on the development of composites with good combined structural and functional properties. Graphical abstract: